SCRUTINIZING COMPLIMENT RESPONSE STRATEGY IN TEACHING ENGLISH AS FOREIGN LANGUAGE IN INDONESIA - Monika Widyastuti Surtikanti (Prasasti: Journal of Linguistics)
Teaching compliment expression might be challenging for Indonesian EFL teacher, especially presenting compliment responses in some certain context of situation. The present study aims at investigating the compliment response strategies in some learning resources used by English teachers in Indonesia. The subjects of this study are the two EFL textbooks written by non-native English speakers and the supplementary materials derived from two Youtube channels and two materials from online learning websites created by native English speakers.The findings revealed accepting was the common compliment response strategy represented in all learning resources. it is also noted that the supplementary materials have various compliment response strategies completed with the meta-pragmatic information on each dialogue. The study implied that the EFL students should be equipped with pragmatic and sociolinguistic information in order to achieve the successful communication.